A mobile isocentric C‐arm for intraoperative cone‐beam CT: Technical assessment of dose and 3D imaging performance. Issue 3 (6th January 2020) - Sheth, N. M.; De Silva, T.; Uneri, A.; Ketcha, M.; Han, R.; Vijayan, R.; Osgood, G. M.; Siewerdsen, J. H.
Abstract : Purpose: To characterize the radiation dose and three‐dimensional (3D) imaging performance of a recently developed mobile, isocentric C‐arm equipped with a flat‐panel detector (FPD) for intraoperative cone‐beam computed tomography (CBCT) (Cios Spin 3D, Siemens Healthineers) and to identify potential improvements in 3D imaging protocols for pertinent imaging tasks. Methods: The C‐arm features a 30 × 30 cm 2 FPD and isocentric gantry with computer‐controlled motorization of rotation (0–195°), angulation (±220°), and height (0–45 cm). Geometric calibration was assessed in terms of 9 degrees of freedom of the x‐ray source and detector in CBCT scans, and the reproducibility of geometric calibration was evaluated. Standard and custom scan protocols were evaluated, with variation in the number of projections (100–400) and mAs per view (0.05–1.65 mAs). Image reconstruction was based on 3D filtered backprojection using "smooth, " "normal, " and "sharp" reconstruction filters as well as a custom, two‐dimensional 2D isotropic filter. Imaging performance was evaluated in terms of uniformity, gray value correspondence with Hounsfield units (HU), contrast, noise (noise‐power spectrum, NPS), spatial resolution (modulation transfer function, MTF), and noise‐equivalent quanta (NEQ). Performance tradeoffs among protocols were visualized in anthropomorphic phantoms for various anatomical sites and imaging tasks. Results: Geometric calibration showed a high degree of reproducibility despite 19 mm gantry flex over a nominal semicircular orbit. The dose for a CBCT scan varied from 0.8–4.7 mGy for head protocols to 6–38 mGy for body protocols. The MTF was consistent with sub‐mm spatial resolution, with f10 (frequency at which MTF = 10%) equal to 0.64 mm −1, 1.0 mm −1, and 1.5 mm −1 for smooth, standard, and sharp filters respectively. Implementation of a custom 2D isotropic filter improved CNR 50–60% for both head and body protocols and provided more isotropic resolution and noise characteristics. The NPS and NEQ quantified the 3D noise performance and provided a guide to protocol selection, confirmed in images of anthropomorphic phantoms. Alternative scan protocols were identified according to body site and task — for example, lower‐dose body protocols (<3 mGy) sufficient for visualization of bone structures. Conclusion: The studies provided objective assessment of the dose and 3D imaging performance of a new C‐arm, offering an important basis for clinical deployment and a benchmark for quality assurance. Modifications to standard 3D imaging protocols were identified that may improve performance or reduce radiation dose for pertinent imaging tasks.